An environmentally responsive layer-by-layer self-assembled nanocomposite and its preparation method and application

Through environmentally responsive layer-by-layer self-assembly nanocomplexes, combined with black phosphorus, polymethformin, hyaluronic acid and P3 peptide modified hyaluronic acid, the existing nanoparticle carriers have poor targeting and low safety in targeting adipocytes and macrophages, achieving multi-modal and dual-targeted treatment for obesity, significantly improving the therapeutic effect.

CN116271096BActive Publication Date: 2025-03-14CHINA PHARM UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310354087.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-04
Publication Date
2025-03-14
Estimated Expiration
2043-04-04

AI Technical Summary

Technical Problem

Existing nanoparticle carriers have poor targeting, low safety in targeting adipocytes and macrophages, and a single treatment model, which limits effective treatment for obesity.

Method used

Environmentally responsive layer-to-layer self-assembled nanocomposites, including black phosphorus nanosheets, polymethformin, hyaluronic acid and P3 peptide modified hyaluronic acid, are used to achieve multimodal and dual-targeted treatment of adipose tissue through layer cladding structure and targeted modification.

Benefits of technology

By targeting fat tissue, the nanocomplex achieves controlled release of drugs, reduces fat content, relieves inflammation, and significantly improves the therapeutic effect on obesity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116271096B_ABST
    Figure CN116271096B_ABST
Patent Text Reader

Abstract

The present invention discloses an environmentally responsive layer-by-layer self-assembled nanocomposite, the nanocomposite includes black phosphorus nanosheets BP, polymetformin PM, hyaluronic acid HA and P3 peptide-modified HA, the nanocomposite is a layer-clad structure, the core is a black phosphorus nanosheet, the middle layer is polymetformin, and the outer layer is hyaluronic acid and P3 peptide-modified HA. The nanocomposite relies on P3 peptide and HA to dual-target adipose tissue, P3-HA can respond to adipose tissue MMP-2 enzyme degradation and expose internal HA, HA can target and bind to multiple CD44 receptors on the surface of agglomerated adipocytes and macrophages, thereby synergizing with PM to inhibit adipogenic gene expression of adipocytes and reduce fat content, reduce the expression level of macrophage inflammatory factors and relieve inflammation, and the photothermal effect of BP also helps to reduce fat accumulation. The environmentally responsive layer-by-layer self-assembled nanocomposite provided by the present invention has good application prospects in obesity treatment drugs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a pharmaceutical preparation and a preparation method and application thereof, and in particular to an environmentally responsive layer-by-layer self-assembly nanocomposite and a preparation method and application thereof. Background Art

[0002] Obesity is a common chronic metabolic epidemic disease. At present, in addition to comprehensive treatments based on diet and exercise, it is mainly treated clinically through surgery and drugs. However, surgery is highly invasive and risky, and the side effects of drugs are serious. Therefore, it is urgent to develop safer and more effective new obesity treatments. Nanoparticles have the advantages of large specific surface area, strong drug loading capacity, high bioavailability, and especially good targeting and adjustable release rate. They have great research prospects in the diagnosis and treatment of obesity and obesity-related metabolic diseases.

[0003] Adipose tissue plays a central role in the development and progression of obesity. It is composed of mature adipocytes and adipocyte precursors, fibroblasts, endothelial cells, stem cells, immune cells, and collagen fibers. Mature adipocytes are the main cells in adipose tissue. They can not only store excess energy in the body in the form of triglycerides (TG), but also have endocrine functions, regulating metabolism by secreting a variety of cytokines (leptin, adiponectin, resistin, and angiotensin, etc.) and inflammatory factors (tumor necrosis factor α and interleukin-6). Excessive TG accumulation leads to an increase in the volume (hypertrophy) and number (hyperplasia) of adipocytes, which are typical signs of the development of obesity.

[0004] In addition, excessive fat accumulation in the body will lead to hypoxia in adipose tissue, disrupting normal metabolism and causing inflammation in adipose tissue. When the TG stored in adipocytes reaches its limit, the cells initiate apoptosis and secrete a large number of chemokines, inducing monocytes in the blood to chemotaxis into adipose tissue, and activating toll-like receptors (TLR) and downstream NF-κB inflammatory pathways, prompting them to polarize into pro-inflammatory M1 macrophages and release a large number of inflammatory factors, such as tumor necrosis factor α, interleukin-6, monocyte chemoattractant protein-1 and transforming growth factor β1, further exacerbating adipose tissue inflammation and inducing systemic inflammation such as insulin resistance.

[0005] There are many nano-therapeutic strategies for fat reduction, most commonly using liposomes, polymer micelles and other carriers to deliver therapeutic drugs to adipose tissue to treat obesity. However, the targeting ability of these nano-carriers is limited, and they cannot effectively deliver therapeutic drugs to adipocytes and macrophages and achieve controlled drug release at the target site; poor targeting ability also reduces the in vivo safety of nanoparticles; these nanoparticles have a single drug loading and simple treatment strategies and methods, which also limits the therapeutic effect of nanoparticles on obesity. Summary of the invention

[0006] Purpose of the invention: This patent provides an environmentally responsive layer-by-layer self-assembled nanocomposite to address the problems of poor targeting of nanoparticle carriers to adipocytes and macrophages, low safety, and a single treatment mode in the prior art. Another purpose of the present invention is to provide a method for preparing the environmentally responsive layer-by-layer self-assembled nanocomposite and its use in preparing obesity treatment drugs.

[0007] Technical solution: The environmentally responsive layer-by-layer self-assembled nanocomposite described in the present invention includes black phosphorus nanosheets (BP), polymetformin (PM), hyaluronic acid (HA) and P3 peptide-modified HA (P3-HA). The nanocomposite is a layer-clad structure, with a core of black phosphorus nanosheets, a middle layer of polymetformin, and an outer layer of hyaluronic acid and P3 peptide-modified HA.

[0008] The PM is prepared by addition reaction of a hydrochloride polymer containing primary or secondary amino groups and a dicyandiamide monomer, wherein the hydrochloride polymer containing primary or secondary amino groups is one of chitosan, linear polyethyleneimine, polylysine, polyethyleneamine or polyallylamine.

[0009] The average molecular weight of the HA is 20-235 kDa.

[0010] The P3 peptide-modified HA is HA modified by the P3 peptide through the MMP-2 substrate peptide chain, and the sequence is HA-PLGLAG-CKGGRAKDC; wherein the MMP-2 substrate peptide chain is the connecting arm.

[0011] The core of the nanocomposite is negatively charged BP with good photothermal conversion ability, the middle layer is positively charged PM, and the outer layer is negatively charged HA with targeting and therapeutic effects and HA modified with P3 peptide with targeting and environmental responsiveness. The PM is an obesity treatment drug.

[0012] The method for preparing the environmentally responsive layer-by-layer self-assembled nanocomposite comprises the following steps:

[0013] (1) Preparation of black phosphorus nanosheets BP: dispersing black phosphorus crystal powder in an acetone solution, ultrasonically exfoliating, centrifuging to remove large black phosphorus crystal precipitates, collecting the upper dispersion and centrifuging again, and suspending the precipitate in water to obtain a water-dispersed BP;

[0014] (2) Preparation of PM: Add hydrochloric acid solution to polymer powder containing primary or secondary amino groups, stir at room temperature, and freeze-dry to obtain hydrochloride polymer; react the hydrochloride polymer with dicyandiamide in an oil bath, cool to room temperature, collect the product solution, dialyze, and freeze-dry to obtain PM:

[0015] (3) Preparation of environmentally responsive layer-by-layer self-assembled nanocomposite P3-HA / PM-BP: black phosphorus nanosheets BP were added dropwise to the PM solution, stirred for reaction and centrifuged, the precipitate was suspended in water, and the PM-BP nanoparticle solution was obtained after sonication; PM-BP nanoparticles were added dropwise to a mixed solution of HA and P3 peptide-modified HA, stirred for reaction and centrifuged, the precipitate was suspended in water, and sonicated to obtain the result.

[0016] In the preparation method, in step (1), the power of ultrasonic exfoliation of the black phosphorus crystal powder is 80 to 200 W; in step (2), the mass ratio of the hydrochloride polymer to dicyandiamide is 1:10 to 1:20; in step (3), the mass ratio of BP, PM, HA and P3 peptide-modified HA is 1:1:1:0.1 to 1:4:4:0.4.

[0017] The application of the environmentally responsive layer-by-layer self-assembled nanocomposite in the preparation of obesity treatment drugs.

[0018] The environmentally responsive layer-by-layer self-assembled nanocomposite is used in the preparation of a drug for reducing fat content in adipose tissue and / or improving inflammation in adipose tissue.

[0019] The application of the environmentally responsive layer-by-layer self-assembled nanocomposite in the preparation of a photothermal combined targeted treatment drug for obesity.

[0020] Preferably, step (1) is specifically as follows: dispersing black phosphorus crystal powder in an acetone solution, placing the dispersion in an ultrasonic probe cell disruptor under ice bath cooling conditions for 24 hours, with a power of 80 to 200 W, and after the end of the ultrasound, centrifuging the dispersion at a low speed to remove unpeeled large black phosphorus crystal precipitates, collecting the upper layer of the dispersion and centrifuging at a high speed to remove the upper layer of acetone organic solvent, and suspending the precipitate with water to obtain a water-dispersed BP.

[0021] Preferably, step (2) is specifically as follows: under magnetic stirring, hydrochloric acid solution is added dropwise to polymer powder containing primary or secondary amino groups, and freeze-dried to obtain hydrochloride polymer; hydrochloride polymer and dicyandiamide are added in a mass ratio of 1:10 to 1:20, and reacted under oil bath stirring conditions. Subsequently, the reaction solution is cooled to room temperature and the product solution is collected, dialyzed for about 48 hours to completely remove excess dicyandiamide, and the dialyzed product is collected and freeze-dried to obtain PM.

[0022] Preferably, step (3) is specifically as follows: the PM solution is transferred into a vial, the black phosphorus nanosheet BP dispersion is added dropwise to the PM solution under stirring conditions, stirred for reaction, and then centrifuged at high speed to remove unbound PM supernatant, the precipitate is suspended in water and ultrasonically dispersed using the probe of an ultrasonic probe cell disruptor to obtain a PM-BP nanoparticle dispersion. Then, the PM-BP nanoparticle dispersion is added dropwise to a mixed solution of HA and P3-HA under stirring conditions for reaction, and then centrifuged at high speed again to remove unbound HA and P3-HA supernatant, the precipitate is suspended in water again and ultrasonically dispersed using the probe of an ultrasonic probe cell disruptor to obtain an environmentally responsive layer-by-layer self-assembled nanocomposite (P3-HA / PM-BP).

[0023] This patent combines the fat-reducing and anti-inflammatory treatment strategies, and combines the physical and chemical characteristics of adipose tissue to prepare an environmentally responsive layer-by-layer self-assembled nano-drug delivery system by combining several raw materials with opposite charges through layer-by-layer electrostatic adsorption and hydrogen bonding, thereby achieving multi-drug, multi-mode, and dual-targeted treatment of obesity, providing new methods and ideas for obesity treatment.

[0024] Principle of the invention: The inventors found in the course of their research that obesity is a chronic metabolic epidemic disease caused by excessive accumulation of body fat due to excessive food intake or changes in the body's metabolism. Excessive fat accumulation leads to fat cell hypertrophy and hyperplasia, which are typical signs of the development of obesity. In addition, excessive fat accumulation will disrupt normal cell metabolism and cause adipose tissue inflammation, which will further lead to complications such as IR, type 2 diabetes, and atherosclerosis. Therefore, reducing fat accumulation in adipocytes and alleviating adipose tissue inflammation are important strategies for obesity treatment. Black phosphorus is a two-dimensional material with excellent photothermal conversion capabilities. It has a large specific surface area, outstanding drug binding and carrying capacity, and is composed only of phosphorus, which can be ultimately oxidized and degraded into non-toxic PO4 in the body. 3-Black phosphorus has good biocompatibility and biosafety, so it is expected to be used as a safe and efficient nano drug carrier for photothermal therapy (PTT), promoting apoptosis of adipocytes and lipolysis to alleviate obesity. Metformin can temporarily and mildly inhibit mitochondrial respiratory chain complex I, destroy cellular ATP synthesis, lead to defects in cyclic adenosine monophosphate and protein kinase A signal transduction, and ultimately activate the AMP-dependent protein kinase (Adenosine 5'-monophosphate (AMP)-activated protein kinase, AMPK) signaling pathway. In adipose tissue, metformin can reduce the levels of peroxisome proliferators-activated receptor gama (PPARγ) and CCAAT / enhancer-binding protein alpha (C / EBPα), key factors of adipogenesis, by activating AMPK, and reduce adipogenesis, enhance TG hydrolysis and free fatty acid (FFA) oxidation, thereby reducing fat masses and lowering blood lipid levels. In addition, metformin can promote the transformation of pro-inflammatory M1 macrophages to anti-inflammatory M2 macrophages by activating the AMPK signaling pathway and reduce the expression level of macrophage inflammatory factors, thereby alleviating adipose tissue inflammation. Because a large number of biguanide groups are grafted into PM molecules, our experiments have proved that PM also has the effect of reducing fat content and relieving inflammation in obesity treatment. Hyaluronic acid (HA) is an acidic polysaccharide naturally present in the extracellular matrix of various tissues. It has good biodegradability and biocompatibility. It can specifically bind to the CD44 receptors on the surface of adipocytes and macrophages and has the ability to target adipose tissue; in addition, studies have found that HA nanoparticles can bind to multiple CD44 receptors on the surface of agglomerated adipocytes and macrophages, respectively, blocking their downstream signaling pathways, thereby inhibiting the expression of adipogenic genes in adipocytes and reducing fat content, and reducing the expression level of macrophage inflammatory factors to relieve inflammation. P3 peptide (CKGGRAKDC) can specifically bind to the antiproliferative protein (PHB) receptors expressed in large quantities on the surface of white adipose tissue blood vessels. Modifying it on the surface of nanoparticles can achieve good targeting ability to adipose tissue.

[0025] Nanoparticles have the advantages of large specific surface area, strong adsorption capacity, high bioavailability, etc., especially good targeting and adjustable release rate, which are beneficial to the diagnosis and treatment of obesity and obesity-related metabolic diseases. Nanoparticle self-assembly based on layer-by-layer binding is an emerging and powerful method for the preparation and construction of nanoparticles. It can alternately deposit charged particles on the charged core through electrostatic binding and hydrogen bonding to achieve modular, universal and flexible preparation of nanoparticles. This type of nanoparticle has many advantages. Each layer of material can be used as both a carrier and a drug, and can be used for multi-drug synergistic delivery, realizing environmentally responsive and controllable drug release.

[0026] Therefore, this patent adopts liquid phase exfoliation to prepare black phosphorus nanosheets BP, and prepares PM by polymers containing primary or secondary amino groups and dicyandiamide under acidic and high temperature conditions, and constructs HA (P3-HA) modified by P3 peptide through MMP-2 substrate peptide chain (connector arm), and then uses BP (-) as the core to alternately bind PM (+), HA and P3-HA (-) with opposite charges to the surface of nanoparticles through layer-by-layer self-assembly technology to prepare P3-HA / PM-BP nanocomposite. The nanocomposite has a layer-cladding structure, the core is a negatively charged nanocarrier BP with good photothermal conversion ability, the middle layer is a positively charged therapeutic drug PM, and the outer layer is a negatively charged HA with targeted and therapeutic effects and a targeted and environmentally responsive P3-HA.

[0027] The nanocomplex is injected into the body through intravenous injection, and reaches the adipose tissue under the dual targeting action of P3 peptide and HA. P3-HA can respond to the degradation of MMP-2 enzyme in adipose tissue and completely expose the internal HA. HA can specifically bind to multiple CD44 receptors on the surface of agglomerated adipocytes and macrophages, thereby inhibiting the expression of adipogenic genes in adipocytes and reducing fat content, reducing the expression level of inflammatory factors in macrophages and relieving inflammation; in addition, enzyme-responsive degradation also promotes the dissociation of nanoparticles and the release of internal drug PM. PM can activate the AMPK signaling pathway to play a lipid-lowering and anti-inflammatory role, while BP can convert 808nm laser into heat energy, destroy the membrane proteins of adipocytes and macrophages, increase the permeability of cell membranes, cause the fat droplets in adipocytes to flow out and reduce fat content, and finally lead to the death of adipocytes and macrophages. This drug delivery system uses a combination of multiple drugs (BP, PM, HA) and multiple treatment modes (chemotherapeutic drug therapy, photothermal therapy) to synergistically treat obesity. It has environmental responsiveness (MMP-2 enzyme) and dual targeting capabilities (P3 peptide and HA), and can show excellent anti-obesity effects.

[0028] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The present invention creatively applies the photothermal conversion ability of BP to the treatment of obesity. BP is not only an excellent drug carrier, but also can be photothermally converted at the targeted site, destroying the adipocyte membrane and causing intracellular lipid droplets to leak, thereby achieving the purpose of reducing fat content. (2) The present invention creatively applies PM to the treatment of obesity. A large number of biguanide groups are grafted into the PM molecule, which can reduce fat content, relieve inflammation and exert an anti-obesity effect similar to metformin. (3) The present invention adopts multiple treatment modes to synergistically treat multiple subjects, combining BP-mediated photothermal therapy with PM and HA-mediated chemical drug therapy, and jointly reducing fat accumulation in adipocytes through different mechanisms, relieving inflammation caused by macrophages. (4) The present invention uses the MMP-2 enzyme substrate peptide chain as a connecting arm to connect HA and P3 peptide, giving the nanoparticles responsiveness to the adipose tissue environment, thereby improving the controlled release and anti-obesity effects of the nanoparticles. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the particle size diagram of BP nanosheets in Example 1;

[0030] Figure 2 is the potential diagram of BP nanosheet in Example 1;

[0031] Figure 3 This is a transmission electron microscope image of BP nanosheets in Example 1;

[0032] Figure 4 This is the appearance of the PM freeze-dried product in Example 2;

[0033] Figure 5 This is the solubility diagram of the PM freeze-dried product in Example 2;

[0034] Figure 6 This is a diagram of the PM color development experiment in Example 2;

[0035] Figure 7 It is the ultraviolet spectrum of PM in Example 2;

[0036] Figure 8 is the Fourier transform infrared spectrum of PM in Example 2;

[0037] Fig. 9 The particle size diagram of the P3-HA / PM-BP nanocomposite in Example 3;

[0038] Fig.10 This is the potential diagram of the P3-HA / PM-BP nanocomposite in Example 3;

[0039] Fig.11 It is the transmission electron microscopy image of the P3-HA / PM-BP nanocomposite in Example 3;

[0040] Fig.12 This is a graph showing the in vitro stability results of the P3-HA / PM-BP nanocomplex in Example 4;

[0041] Fig.13 This is a graph showing the results of MMP-2 enzyme responsive release of the P3-HA / PM-BP nanocomplex in Example 5;

[0042] Fig.14 This is the Oil Red O staining of 3T3-L1 cells by different nanocomplexes in Example 6;

[0043] Fig.15 This is a graph showing the polarization of different nanocomposites on RAW264.7 cells in Example 7;

[0044] Fig.16 This is a graph showing the effect of different nanocomplexes in Example 8 on the expression level of inflammatory factor TNF-α in RAW264.7 cells;

[0045] Fig.17 This is a graph showing the effects of different nanocomplexes in Example 8 on the expression level of inflammatory factor IL-1β in RAW264.7 cells. DETAILED DESCRIPTION

[0046] The technical scheme of the present invention is further described below in conjunction with the accompanying drawings. The materials and reagents used in the following examples can all be obtained from commercial sources.

[0047] Example 1

[0048] Preparation and properties of black phosphorus nanosheets (BP)

[0049] (1) Preparation of black phosphorus nanosheets (BP)

[0050] 15.00 mg of black phosphorus crystal powder was accurately weighed and dispersed in an acetone solution. The dispersion was placed in an ultrasonic probe cell disruptor. Under ice bath cooling conditions, the power was gradually increased from 80 W to 200 W, and the ultrasound was continued for 24 h. After the ultrasound was completed, the dispersion was transferred to a 2 mL EP tube and centrifuged at low speed for 1 min to remove the unpeeled large black phosphorus crystal precipitate. The upper dispersion was collected and transferred to a 2 mL EP tube again. The upper acetone organic solvent was discarded by high-speed centrifugation, and the precipitate was suspended with deionized water to obtain a water-dispersed BP.

[0051] (2) Study on the properties of black phosphorus nanosheets (BP)

[0052] The particle size of BP was measured by dynamic light scattering (DLS). Figure 1The particle size is (173.5±5.2) nm. The Zeta potential of BP was measured by electrophoretic light scattering (ELS) method. Figure 2 As shown in Figure 1, BP is negatively charged with a potential of (-15.12+1.61) mV. The results of transmission electron microscope (TEM) observation are shown in Figure 1. Figure 3 As shown, BP presents a thin flake structure with a smooth surface and a uniform particle size distribution of about 150 nm.

[0053] Example 2

[0054] Preparation and properties of polymetformin (PM)

[0055] (1) Preparation of polymetformin (PM)

[0056] Weigh 10 g of polymer powder containing primary or secondary amine groups (chitosan, linear polyethyleneimine, polylysine, polyethyleneamine, polyallylamine), add hydrochloric acid solution dropwise thereto under magnetic stirring, stir at room temperature until it is basically dissolved into a gelatinous state, then transfer the gelatinous substance to a glass dish, and freeze-dry to obtain the hydrochloride polymer.

[0057] Weigh 1g of the hydrochloride polymer prepared above and 15g of dicyandiamide (excess) in a three-necked flask, place the flask in an oil bath, add 15mL of hydrochloric acid solution and 5mL of deionized water, and continue the reaction for 5h. Then take the three-necked flask and let it air to room temperature, collect the product solution in the bottle, place it in a dialysis bag with a molecular weight cutoff of 3500Da, and dialyze it for about 48h with ultrapure water as the dialysis medium to completely remove the excess dicyandiamide. After the dialysis is completed, collect the dialyzed product, and freeze-dry it for about 48h to obtain PM.

[0058] (2) Study on the properties of polymethformin (PM)

[0059] The appearance of PM freeze-dried product is Figure 4 As shown, it is a light yellow tough solid that is not easy to absorb moisture; take an appropriate amount of PM and dissolve it in deionized water to examine its solubility. The results are as follows Figure 5 As shown in the figure, compared with the turbid hydrochlorinated chitosan solution (HCl-CS), the PM solution is clear and transparent, and its solubility is significantly improved. 10% (w / v) sodium nitroprusside (sodium nitrosoferrocyanide), 10% (w / v) potassium hexaferrite (III) and 10% (w / v) NaOH solution were mixed in equal volumes to prepare a colorimetric agent, and metformin was used as a positive control to investigate whether guanidine groups were introduced into PM by colorimetric reaction. The results are shown in the figure. Figure 6 As shown in the figure, similar to Metformin, PM has an obvious guanidine color reaction, and as the concentration increases, the solution reaction color gradually deepens, while HCl-CS has no color change, proving that guanidine groups have been successfully introduced into PM, preliminarily proving that PM preparation is successful. The PM solution was scanned by UV-visible spectrophotometer to observe its characteristic absorption peaks. The results are shown in the figure. Figure 7 As shown, PM has a maximum absorption at a wavelength of 234 nm, which is the same as the biguanide absorption peak of metformin, while HCl-CS has no characteristic absorption at this wavelength, indicating that the biguanide group was successfully introduced into PM, preliminarily proving that PM was successfully prepared. Figure 8 This is the Fourier transform infrared spectrum of PM. It can be seen that it is close to the characteristic absorption peaks of metformin. PM has peaks at 1651, 1558 and 1381 cm -1 There are obvious biguanide characteristic absorption peaks at the wavenumbers, corresponding to the guanidine C=N stretching vibration, CNC and -NH 2+ The bending vibration absorption peak at 100 nm was found, while HCl-CS had no obvious absorption at this wave number, which indicated that the biguanide group was successfully connected to chitosan and PM was successfully prepared. The grafting rate of the biguanide group in PM was detected by an organic element analyzer. It was known that the molecular formula of the chitosan monomer was C6H 11 O4N, Mn is 161; the molecular formula of chitin monomer is C8H 13 O5N, Mn is 203; the molecular formula of PM monomer is C8H 15 O4N5, Mn is 245. The deacetylation degree of chitosan used to synthesize PM is 87.50%, and the proportion of chitin monomer in the chitosan polymer molecule is 12.50%.

[0060] According to the measured values ​​of the mass percentage (%) of C and N elements obtained by organic element analysis listed in Table 1, the grafting rate of PM was calculated to be 20.00%.

[0061] Table 1 is the PM grafting rate test results

[0062]

[0063] Example 3

[0064] The P3-HA sequence is HA-PLGLAG-CKGGRAKDC, which was purchased from Shanghai Qiangyao Biotechnology Co., Ltd.; among them, "-" is an amide bond, the average molecular weight of HA is 20-235 kDa, and the carboxyl group of hyaluronic acid and the amino group of proline form an amide bond.

[0065] Preparation and Properties of P3-HA / PM-BP Nanocomposites

[0066] (1) Preparation of P3-HA / PM-BP nanocomposites

[0067] 1 mL of 0.6 mg / mL PM solution was transferred to a vial, and then 0.2 mg of BP dispersion was precisely measured and added dropwise to the PM solution under stirring for reaction, and then centrifuged at high speed to remove the unbound PM supernatant, and the precipitate was suspended with 1 mL of deionized water, placed in an ultrasonic probe cell disruptor, and ultrasonically dispersed for 10 min under ice bath cooling conditions to obtain PM-BP nanoparticle solution. Then 1 mL of 0.6 mg / mL HA solution and 50 uL of 1.2 mg / mL P3-HA mixed solution were transferred to a vial, and the above PM-BP nanoparticles were added dropwise thereto under stirring conditions, and after stirring the reaction, the unbound HA and P3-HA supernatant were centrifuged again at high speed to remove the unbound HA and P3-HA supernatant, and the precipitate was resuspended with 1 mL of deionized water, and the dispersion was placed in an ultrasonic probe cell disruptor, and ultrasonically dispersed for 10 min under ice bath cooling conditions to obtain the final P3-HA / PM-BP nanocomposite.

[0068] (2) Study on the properties of P3-HA / PM-BP nanocomposites

[0069] The particle size of the prepared P3-HA / PM-BP nanocomposite was measured by DLS method. Fig. 9 The Zeta potential was measured by ELS method, and the results are as follows Fig.10 As shown, the potential of BP is (-15.12+1.61) mV, the potential of PM-BP is (19.95±3.12) mV, the potential of HA / PM-BP is (-27.44±2.49) mV, and the potential of P3-HA / PM-BP nanoparticles is (-29.36±4.28) mV. From BP to PM-BP, and then to HA / PM-BP, the potential is reversed once each time a substance is coated. This proves that PM and HA are successfully modified on BP layer by layer. Due to the influence of the trace negative charge of P3 peptide, the potential of P3-HA / PM-BP nanoparticles is slightly lower than that of HA / PM-BP nanoparticles, which also shows that P3 peptide is adsorbed to the surface of nanoparticles and P3-HA / PM-BP nanoparticles are successfully prepared. TEM observation results are shown in Fig.11 As shown, P3-HA / PM-BP nanoparticles are thick lamellar structures with spot distribution on the surface, and the particle size is about 250 nm.

[0070] Example 4

[0071] Study on the in vitro stability of P3-HA / PM-BP nanocomposites

[0072] Take an appropriate amount of P3-HA / PM-BP nanocomplex solution, add it to water, PBS (pH 7.4) and cell culture medium (DMEM containing 10% fetal bovine serum), respectively, seal it after nitrogen aeration and place it in a 4°C environment, measure the particle size of the nanoparticles at 0, 1, 2, 3, 4, 5, and 6 days, and calculate the particle size change of the nanoparticles according to the following formula.

[0073]

[0074] Among them, D0, D t are the particle sizes of the nanoparticles at the initial time and after standing for t hours, respectively.

[0075] The results are as follows Fig.12 As shown, with the extension of dispersion time, the particle size of P3-HA / PM-BP nanocomplex in different dispersion media fluctuated, but the particle size change was less than 10%, indicating that P3-HA / PM-BP nanocomplex had good in vitro stability and was expected to remain stable in the blood environment.

[0076] Example 5

[0077] Study on the responsive release characteristics of P3-HA / PM-BP nanocomplex to MMP-2

[0078] Weigh 2 portions of 2 mL of L-HA / PM-BP nanocomplex aqueous dispersion and place them in two dialysis bags with a molecular weight cutoff of 1000 kDa. Add 10 nM recombinant human matrix metalloproteinase-2 (rhMMP-2) to one of the dialysis bags. Then place the two dialysis bags in 50 mL of PBS (pH 7.4) release medium and release at (37 ± 0.5) °C and 100 rpm for 24 h. During this period, 2 mL of release medium containing released drugs was taken out at 0, 1, 2, 4, 8, 12, and 24 h, and 2 mL of fresh release medium was added in time. Subsequently, the absorbance of the sample at a wavelength of 234 nm was detected by ultraviolet spectrophotometer, and the PM content released was calculated. The release curve was drawn with the sampling time as the horizontal axis and the percentage of drug release as the vertical axis.

[0079] Fig.13Figure 2 shows the PM release of nanoparticles with and without rhMMP-2. It can be seen that when rhMMP-2 is present, the PM release rate is faster, with a cumulative release of about 90% at 8 hours, while when rhMMP-2 is absent, the PM release rate is slower, with a cumulative release of less than 50% at 24 hours. The P3-HA of the P3-HA / PM-BP nanocomplex is connected to the MMP-2 substrate peptide chain (PLGLAG), which can be degraded by MMP-2, resulting in the exposure of the internal HA, accelerating the dissociation of the nanoparticles and the release of PM; when there is no MMP-2, the outer layer of P3 peptide wrapping plays a protective role, and the nanoparticles are relatively stable. However, because the nanoparticles are essentially formed mainly through electrostatic adsorption and hydrogen bonding, the stability is slightly worse than that of liposomes and other encapsulated structures, so about 50% of PM is still released at 24 hours. In summary, the P3-HA / PM-BP nanocomplex still exhibits a high MMP-2 responsive release characteristic, which is conducive to its better function in adipose tissue in vivo.

[0080] Example 6

[0081] Study on the anti-obesity effect of P3-HA / PM-BP nanocomplex on 3T3-L1 in vitro

[0082] 3T3-L1 cells in the logarithmic growth phase were seeded in a 24-well plate, and an uninduced control group (Control) and induced different drug-dosing groups (PBS, BP, PM, PM-BP, HA / PM-BP, P3-HA / PM-BP, P3-HA / PM-BP+Laser) were set up, with 3 replicate wells in each group. The cells were cultured in an incubator until contact inhibition for 2 days before drug administration. Induction medium I (DMEM complete medium containing 0.5 mM 3-isobutyl-1-methylxanthine (IBMX), 1 μM dexamethasone (DEX), and 10 μg / mL insulin (ISN)) was used to prepare solutions containing 30 μg / mL (in terms of phosphorus content) of BP, PM-BP, HA / PM-BP, and P3-HA / PM-BP nanocomplexes, and a solution containing 0.02 mg / mL PM. Using PBS as a control, 1 mL of the drug solution was added to each well of cells for 4 consecutive days, followed by induction medium II (DMEM complete medium containing 10 μg / mL ISN) for continued culture for 4 days, and then changed to DMEM complete medium. The illumination group was irradiated (808 nm, 1.5 W / cm 2 , 10min), and continued to culture for 48h after the illumination ended. Finally, the cells in each group were stained with Oil Red O and observed and photographed.

[0083] Oil red O staining results Fig.14As shown in the figure, the uninduced control group had no lipid droplets, while the blank control group treated with PBS had the most lipid droplets, indicating that 3T3-L1 cells can be successfully induced into mature adipocytes without drug interference. Compared with the PBS group, both PM and PM-BP significantly reduced the content of lipid droplets, indicating that PM has a good fat-reducing effect; compared with the PM-BP group, the HA / PM-BP nanocomplex further reduced the content of lipid droplets, which may be due to the specific binding and aggregation of HA on the surface of the nanoparticles with the CD44 receptor on the surface of the 3T3-L1 cells, which inhibited the downstream adipogenic pathway. In addition, the specific binding of HA to the CD44 receptor on the surface of 3T3-L1 cells also contributes to the targeted uptake of nanoparticles by cells, further improving the therapeutic effect of HA / PM-BP; after treatment with the P3-HA / PM-BP nanocomplex, cells Compared with the HA / PM-BP group, the intracellular lipid droplet content is further reduced. This is because the targeted P3 peptide is modified in the nanocomplex, which can further improve the targeted uptake of the nanocomplex by 3T3-L1 cells, thereby prompting more nanocomplexes to enter adipocytes to exert anti-obesity effects. Compared with the P3-HA / PM-BP group, the lipid droplet content of cells treated with P3-HA / PM-BP+Laser is further reduced. This is because BP generates heat energy after 808nm laser irradiation. The high temperature destroys the permeability of the adipocyte membrane, causing cell shrinkage, lysis, and death, and the leakage of intracellular lipid droplets further reduces the fat content. Therefore, the P3-HA / PM-BP combined treatment group can reduce the fat content in 3T3-L1 cells to the greatest extent and has the best in vitro anti-obesity effect.

[0084] Example 7

[0085] Study on the polarization effect of P3-HA / PM-BP nanocomplex on RAW264.7 cells

[0086] RAW264.7 cells in the logarithmic growth phase were inoculated in a 6-well plate, with 1 mL in each well. A control group (Control) without lipopolysaccharide (LPS) polarization and a drug administration group (PBS, BP, PM, PM-BP, HA / PM-BP, P3-HA / PM-BP and P3-HA / PM-BP+Laser) polarized with LPS were set up respectively. The cells were cultured in an incubator and drug administration began when the cells were polarized to 70-80%. DMEM complete medium was used to prepare solutions containing 30 μg / mL (in terms of phosphorus content) of BP, PM-BP, HA / PM-BP and P3-HA / PM-BP nanocomplexes, and solutions containing 0.02 mg / mL PM. PBS was used as a control. 1 mL of the drug solution was added to each well of cells and cultured for 24 hours. The illumination group was illuminated (808 nm, 1.5 W / cm2, 10 min). After the illumination ended, 1 mL of DMEM complete medium containing 1 μg / mL LPS was replaced and cultured for another 24 hours, i.e., the drug administration ended. After that, the cells in each well were digested and collected, and incubated with PE-labeled anti-CD86 antibody and APC-labeled anti-CD206 antibody, and the fluorescence intensity was detected by flow cytometry. The results of macrophage polarization are shown in Figure 2. Fig.15 As shown in the figure, compared with the PBS control group, both PM and PM-BP can significantly reduce the proportion of macrophage M1, and significantly increase the proportion of M2, so that the M2 / M1 ratio increased significantly, indicating that PM has a good effect of promoting anti-inflammatory M2 polarization; compared with PM-BP, HA / PM-BP, P3-HA / PM-BP and P3-HA / PM-BP+Laser treatments can further increase the M2 / M1 ratio, which may be due to the increase in the cell uptake of nanoparticles caused by the binding of HA to the CD44 receptor on the surface of RAW264.7 cells, and because RAW264.7 cells do not express PHB receptors, P3-HA / PM-BP did not significantly increase the M2 / M1 ratio. This shows that HA / PM-BP, P3-HA / PM-BP and P3-HA / PM-BP+Laser groups all have good effects of promoting M2 polarization, and are expected to play a good role in anti-inflammatory and obesity treatment.

[0087] Example 8

[0088] Study on the expression level of inflammatory factors in RAW264.7 cells by P3-HA / PM-BP nanocomplex

[0089] RAW264.7 cells in the logarithmic growth phase were seeded in 24-well plates, 1 mL per well, and a control group (Control) without LPS polarization and a drug-treated group (PBS, BP, PM, PM-BP, HA / PM-BP, P3-HA / PM-BP and P3-HA / PM-BP+Laser) with LPS polarization were set up respectively. The cells were placed in an incubator and cultured until 70-80% of the cells were dosed. A solution containing 30 μg / mL (in terms of phosphorus content) of BP, PM-BP, HA / PM-BP and P3-HA / PM-BP nanocomplexes and a solution containing 0.02 mg / mL PM were prepared using DMEM complete medium. PBS was used as a control, and 0.5 mL of the drug solution was added to each well of cells and cultured for 24 hours, then replaced with 0.5 mL of DMEM complete medium containing 1 μg / mL LPS, and the illumination group was illuminated (808 nm, 1.5 W / cm 2 After the illumination ended, the culture was continued for 24 h, and the administration was terminated. The upper culture medium in each well was then collected, and the impurities were removed by centrifugation at 2000 rpm for 20 min to obtain the supernatant sample, and the content of TNF-α and IL-1β proteins was detected according to the method indicated in the ELISA kit instructions.

[0090] Fig.16Figure 3 is the effect of different nanocomplexes on the expression of TNF-α by macrophages. The TNF-α concentration of the Control group was only (111.41±7.42) pg / mL without LPS polarization, while the concentration of the PBS group after LPS polarization increased to (443.01±15.64) pg / mL, indicating that after LPS polarization treatment, the secretion of inflammatory factors by RAW264.7 macrophages increased and turned to pro-inflammatory direction; compared with the PBS group, the concentration of TNF-α in the PM group was (360.70±10.12) pg / mL, and the content was significantly decreased, indicating that PM has a good anti-inflammatory effect; compared with the PM-BP group with a TNF-α concentration of (320.90±4.17) pg / mL, the concentration of the HA / PM-BP group was significantly decreased to (275.70±4.75) pg / mL, because HA can bind to the surface of macrophages. The specific binding of CD44 receptors can aggregate CD44 and inhibit the downstream inflammatory pathways, and mediate more nanoparticles to enter the cells to play a role, so the level of inflammatory factors is greatly reduced; the TNF-α concentration of the P3-HA / PM-BP group is (263.53±1.66) pg / mL, which is not significantly different from the HA / PM-BP group. This is because the P3 peptide-specific receptor PHB is not expressed on the surface of RAW264.7 cells, and the cell uptake of the nanocomplex is not significantly increased, so there is no significant difference in the effect; and the concentration of TNF-α in the final drug-treated group P3-HA / PM-BP+Laser is higher than that of the non-irradiated group, which is (304.42±10.80) pg / mL. This may be because the photothermal treatment causes partial apoptosis of macrophages, and the apoptotic cells appropriately activate the inflammatory response of macrophages, causing them to secrete more TNF-α inflammatory factors within a certain period of time. But overall, compared with the PBS group, P3-HA / PM-BP+Laser has a better ability to express anti-inflammatory factors and a better anti-inflammatory effect. Fig.17Figure 3 shows the effect of different nanocomplexes on the expression of IL-1β in macrophages. The concentration of the Control group without LPS polarization was (14.80±0.53) pg / mL, while the concentration of the PBS group after LPS polarization was (86.13±4.29) pg / mL, which was significantly increased. This also shows that after LPS polarization, RAW264.7 macrophages transform toward pro-inflammatory direction and can secrete a large number of inflammatory factors, which is consistent with the results of literature research. In addition, BP, PM, PM-BP, HA / PM-BP, P3-HA / PM-BP and P The IL-1β protein contents in the 3-HA / PM-BP+Laser group were (72.22±2.05) pg / mL, (61.93±0.53) pg / mL, (56.69±0.86) pg / mL, (45.06±2.46) pg / mL, (37.93±2.02) pg / mL and (46.58±3.47) pg / mL, respectively. The changing trend of IL-1β concentration was basically consistent with that of TNF-α, which together proved that the P3-HA / PM-BP+Laser group had a better anti-inflammatory effect.

Claims

1. An environmentally responsive layer-by-layer self-assembled nanocomposite, characterized in that: The invention comprises black phosphorus nanosheets BP, polymetformin PM, hyaluronic acid HA and HA modified with P3 peptide. The nanocomposite is a layer-clad structure, the core is black phosphorus nanosheets, the middle layer is polymetformin, and the outer layer is hyaluronic acid and HA modified with P3 peptide; the PM is prepared by addition reaction of a hydrochloric acid polymer containing primary or secondary amino groups and a dicyandiamide monomer, the hydrochloric acid polymer containing primary or secondary amino groups is one of chitosan, linear polyethyleneimine, polylysine, polyethyleneamine or polyallylamine; the average molecular weight of the HA is 20-235 kDa; the HA modified with P3 peptide is The HA modified by the MMP-2 substrate peptide chain has a sequence of HA-PLGLAG-CKGGRAKDC; wherein the MMP-2 substrate peptide chain is a connecting arm; the nanocomposite is prepared by the following method: liquid phase exfoliation is used to prepare black phosphorus nanosheets BP, PM is prepared by a polymer containing primary amino groups or secondary amino groups and dicyandiamide under acidic high temperature conditions, and HA modified by the MMP-2 substrate peptide chain of the P3 peptide is constructed, and then PM, HA, and P3-HA are alternately combined on the surface of the nanoparticles by layer-by-layer self-assembly technology with the negatively charged BP as the core to prepare the P3-HA / PM-BP nanocomposite.

2. The nanocomposite according to claim 1, characterized in that The core of the nanocomposite is negatively charged BP with good photothermal conversion ability, the middle layer is positively charged PM, and the outer layer is negatively charged HA with targeting and therapeutic effects and HA modified with P3 peptide with targeting and environmental responsiveness.

3. The method for preparing the environmentally responsive layer-by-layer self-assembled nanocomposite according to claim 1, characterized in that: The following steps are involved: (1) Preparation of black phosphorus nanosheets BP: black phosphorus crystal powder is dispersed in an acetone solution, ultrasonically exfoliated, and centrifuged to remove large black phosphorus crystal precipitates. The upper dispersion is collected and centrifuged again, and the precipitate is suspended in water to obtain a water-dispersed BP; (2) Preparation of PM: adding hydrochloric acid solution to polymer powder containing primary or secondary amino groups, stirring at room temperature, and freeze-drying to obtain hydrochloride polymer; reacting the hydrochloride polymer with dicyandiamide in an oil bath, cooling to room temperature, collecting the product solution, dialyzing, and freeze-drying to obtain PM; (3) Preparation of environmentally responsive layer-by-layer self-assembled nanocomposite P3-HA / PM-BP: black phosphorus nanosheets BP were added dropwise into the PM solution, stirred for reaction and centrifuged, the precipitate was suspended in water, and the PM-BP nanoparticle solution was obtained after sonication; PM-BP nanoparticles were added dropwise into the mixed solution of HA and P3 peptide-modified HA, stirred for reaction and centrifuged, the precipitate was suspended in water, and sonicated to obtain the result.

4. The method according to claim 3, characterized in that: In step (1), the power of ultrasonic exfoliation of the black phosphorus crystal powder is 80-200 W; in step (2), the mass ratio of the hydrochloric acid polymer to dicyandiamide is 1:10-1:20; in step (3), the mass ratio of BP, PM, HA and P3 peptide-modified HA is 1:1:1:0.1-1:4:4:0.

4.

5. Use of the environmentally responsive layer-by-layer self-assembled nanocomposite according to claim 1 in the preparation of a drug for treating obesity.

6. Use of the environmentally responsive layer-by-layer self-assembled nanocomposite according to claim 1 in the preparation of a drug for reducing fat content in adipose tissue and / or improving inflammation in adipose tissue.

7. Use of the environmentally responsive layer-by-layer self-assembled nanocomposite according to claim 1 in the preparation of a photothermal combined targeted treatment drug for obesity.

Citation Information

Patent Citations

  • Fat tissue targeting peptide P3-chitosan oligosaccharide lactate-polyethylene glycol delivery system and application of system in nucleic acid drug delivery

    CN111388452A

  • Antibody-modified anti-tumor targeted drug delivery and combined treatment system as well as preparation method and application thereof

    CN114796491A